Visual search without central vision – no single pseudofovea location is best - Angelika Lingnau; Thorsten Albrecht; Jens Schwarzbach; Dirk Vorberg (Journal of Eye Movement Research)
We typically fixate targets such that they are projected onto the fovea for best spatial resolution. Macular degeneration patients often develop fixation strategies such that targets are projected to an intact eccentric part of the retina, called pseudofovea. A longstanding debate concerns which pseudofovea-location is optimal for non-foveal vision. We examined how pseudofovea position and eccentricity affect performance in visual search, when vision is restricted to an off-foveal retinal region by a gaze-contingent display that dynamically blurs the stimulus except within a small viewing window (forced field location). Trained normally sighted participants were more accurate when forced field location was congruent with the required scan path direction; this contradicts the view that a single pseudofovea location is generally best. Rather, performance depends on the congruence between pseudofovea location and scan path direction.